2005
DOI: 10.1111/j.1398-9995.2005.00795.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of IgE‐binding epitopes on gliadins for patients with food allergy to wheat

Abstract: B epitopes in wheat allergy were different from B epitopes of coeliac disease. Differences exist in IgE-binding epitopes between patients with food allergy to wheat. IgE from those suffering from WDEIA, anaphylaxis and urticaria detected sequential epitopes in the repetitive domain of gliadins whereas IgE from AEDS patients probably recognized conformational epitopes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
145
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(159 citation statements)
references
References 37 publications
10
145
0
2
Order By: Relevance
“…[10], [120], [121], [122] and [123] [124], [125], [126], [127], [128], [129] and [130] However, other studies at different shifting offsets, with different peptides sizes, or both revealed different sets of immunodominant sequential epitopes for the same allergens. [29], [124], [125], [126], [127], [130] and [131] Nevertheless, approaches to use these alleged immunodominant peptides for the risk assessment of life-threatening symptoms, as well as the prediction of persistence in food hypersensitivity, were apparently successful.…”
Section: Diagnosis Of Food Allergy With Synthetic Sequential Epitopesmentioning
confidence: 99%
See 2 more Smart Citations
“…[10], [120], [121], [122] and [123] [124], [125], [126], [127], [128], [129] and [130] However, other studies at different shifting offsets, with different peptides sizes, or both revealed different sets of immunodominant sequential epitopes for the same allergens. [29], [124], [125], [126], [127], [130] and [131] Nevertheless, approaches to use these alleged immunodominant peptides for the risk assessment of life-threatening symptoms, as well as the prediction of persistence in food hypersensitivity, were apparently successful.…”
Section: Diagnosis Of Food Allergy With Synthetic Sequential Epitopesmentioning
confidence: 99%
“…[29], [124], [125], [126], [127], [130] and [131] Nevertheless, approaches to use these alleged immunodominant peptides for the risk assessment of life-threatening symptoms, as well as the prediction of persistence in food hypersensitivity, were apparently successful. In wheat-dependent exerciseinduced anaphylaxis, all sera from affected patients showed significant sIgE reactivity to the respective peptides, whereas none of the sera from nonatopic control subjects demonstrated reactivity, and sera from control patients with atopic dermatitis showed very low to nonexistent reactivity.…”
Section: Diagnosis Of Food Allergy With Synthetic Sequential Epitopesmentioning
confidence: 99%
See 1 more Smart Citation
“…LMW glutenins play an important role in the development of immediate hypersensitivity to hydrolyzed wheat proteins (IHHWPs) baker's asthma, atopic dermatitis and EIWA [18,20]. Battais et al showed elevated levels of IgE antibodies against all GP in the sera of 28 patients with atopic dermatitis, asthma, urticaria and eczema, which suggested that these proteins were important factors contributing to disease development [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Several wheat allergens have been described and some of them associated with different clinical features presented by the patient [9]. Thus, α-amylase/trypsin inhibitor, serine proteinase, thaumatin-like proteins, prolamins, and peroxidases have been involved with baker's asthma, urticaria/angioedema and cutaneous symptoms associated with atopic dermatitis; ω-5-gliadin (Tri a 19) has been related with exercise-induced anaphylaxis, and nonspecific lipid transfer protein (nsLTP or Tri a 14) with allergy symptoms upon ingestion of wheat, among others [7,8].…”
Section: Discussionmentioning
confidence: 99%